Prognostic Directions of Preparation of the Future Educators of Pre-School Educational Establishments to the Work with Deadapted Children (by the Results of Forming Experiment) - Larysa Zdanevych (Pedagogical Discourse, 2014)
In the article by the results of forming experiment, which was conducted during 2009-2013, prognostic directions of preparation of the future educators of pre-school educational establishments to the work with deadapted children have been grounded. The author singles out components, which level of maturing indicates the quality of preparation of the future educators of pre-school educational establishments to the work with deadapted children, namely: motivation-valuable, (directed to the achievement, motivational conviction, presence of positive motivation to the study of adapted technologies of development, teaching and upbringing deadapted children), cognitive-technological (independence, professional competence and accuracy of fulfillment actions, knowledge of modern methods of diagnostics and technologies of development, teaching and upbringing deadapted children), information-communicative (awareness of the future educators of pre-school educational establishments of communicative activity, communicative readiness to the dialogue and inclination to communication, effectiveness of using adapted technologies of interaction with preschool children), and reflective-self-educational (necessity in mastering personal characteristics and professional qualities, ability to self-education and self-development, ability to reflexion, self-control and correction of the process and result of work with deadapted children).